Rare Presentation of Neonatal Necrotizing Fasciitis: Case Series and Review of Literature - Kruti N Shah; Shwetal Bhatt; Dipal Zanzrukriya; Salesh K Soni (Pediatric Infectious Disease)
Aims and background: Necrotizing fasciitis is a rare, severe, fulminating disorder infecting all the layers of skin and extending to the fascial planes and muscular layer. It is an unusual presentation of septicemia in neonates and is, to a larger extent, a disease of immunocompromised adults. Thus, there is a lack of reported neonatal cases. It could be misdiagnosed as cellulitis or myonecrosis due to its nonspecific presentations. It becomes essential to diagnose in a timely manner and culminate in a multidisciplinary approach with antimicrobial treatments and surgical aid to prevent its fulminating course. Thus, we aim to report three cases of necrotizing fasciitis presented in neonatal age, presented to us within a short span of 6 months, and sensitize its neonatal presentation with distinct clinical features. Case description: We report three cases of necrotizing fasciitis presented in neonatal age with varied clinical features, presenting as deep ulcers with fasciitis and scalp abscesses with no history of perinatal infections. The wound culture may not necessarily be septic. However, a multidisciplinary approach involving broad-spectrum intravenous antimicrobial therapy with advanced plastic surgical methodologies can help attenuate its fulminant course. Timely diagnosis and prompt intervention may aid in complete recovery, as in our cases, and thus prevent fatality. Conclusion: Neonatal necrotizing fasciitis is a progressive, fulminating infection of the skin, subcutaneous tissues, and fascial planes and may extend to muscular levels. We aim to sensitize the presence of necrotizing fasciitis as an unusual presentation of neonatal septicemia, encourage prompt diagnosis, and adopt a multidisciplinary approach. Clinical significance: Neonatal necrotizing fasciitis, though infrequent, carries a fatal, fulminating course. It is primarily a polymicrobial infection involving deep skin layers with extension to muscular planes. The diagnosis is usually clinical. Timely diagnosis with prompt antimicrobial treatment and surgical intervention helps reduce grave complications and mortality rates.